KORELASI POLA ASUH ORANG TUA TERHADAP PERILAKU SOSIAL PESERTA DIDIK DI SD MUHAMMADIYAH 9 PALEMBANG - Okta Siliani; Middya Boty; Djoko Rohadi Wibowo (STKIP Subang, 2026)
This study aims to determine the relationship between democratic parenting styles and the social behavior of students at SD Muhammadiyah 9 Palembang. This study uses a quantitative approach with a correlational research design. The research subjects consisted of 33 parents and 33 sixth-grade students at SD Muhammadiyah 9 Palembang in the odd semester of the 2025/2026 academic year. The sampling technique used saturated sampling. Data collection was conducted through a Likert scale questionnaire, observation, and documentation. The research instruments had undergone validity and reliability tests, with a Cronbach's Alpha value of 0.679 for the variable of democratic parenting and 0.762 for the variable of student social behavior, thus declared reliable. The results of descriptive statistical analysis showed that the average score for democratic parenting was 55.21 and the average score for student social behavior was 77.27, both of which were in the fairly good category. The results of the Pearson Product Moment correlation test showed a correlation coefficient of 0.943, indicating a very strong and positive relationship between democratic parenting and student social behavior. A significance value of 0.000 < 0.05 indicates that the relationship is statistically significant. Based on these research results, it can be concluded that democratic parenting has a very strong and significant relationship with students' social behavior.